Spontaneous thrombosis of a vein of galen malformation - Mohanty, Chandan B. (Asian J Neurosurg, 2016)
Vein of Galen malformation (VOGM) is a rare congenital vascular anomaly, comprising about 1% of all intracranial vascular anomalies, predominantly affecting the children less than 1 year of age. A 6-month-old infant presented with complaints of increasing head size of 3 months duration and multiple episodes of vomiting associated with refusal to feed since 7 days. He was a known case of VOGM who had initially refused treatment. Investigations revealed a spontaneously thrombosed VOGM with obstructive hydrocephalous. Child improved uneventfully with ventriculoperitoneal shunt. Spontaneous thrombosis of a VOGM is a rare occurrence and carries a better prognosis. The relevant literature is discussed with emphasis on etiopathogenesis, mechanism, and management of spontaneous thrombosis of the malformation.